The social representations of entrepreneurial work and the professions orientation of the university student, a field study On a sample of students of the Faculty of Humanities and Social Sciences at the University of Jijel - Abdenour, Moussa; Achour, Allouti; Nekbil, Abdelmalih (The journal of contemporary issues in business and government, 2023)
The study aimed to test the relationship between the variable of social representations of entrepreneurial work in its dimensions (professional identity, the image of work as a moral value) and the variable of professional orientation of the university student, at the Faculty of Humanities and Social Sciences at Mohammad ben Yahya University in the state of Jijel, and the descriptive approach was relied upon, as a questionnaire was distributed to a sample A stratified random sample of one hundred twenty (120) individuals, where they were analyzed statistically using the Statistical Packages for Social Sciences program.(SPSS). The results showed that there is no statistically significant relationship between the professional identity and the professional decision-making of the university student, and that there is a weak direct relationship between the image of work as a moral value and professional maturity. When there are no statistically significant differences due to the variable of age, family status, and the place of residence.